Megachurches and the problem of leadership: An analysis of the encounter between the Evangelical world and Politics in Argentina - Algranti, Joaquin Maria (2012)
Researchers usually address the political aspect of Evangelical groups by highlighting their involvement in party politics: their ability to create new organisations or form alliances with existing ones, introducing into the electoral field the assumption of a more or less homogeneous or easily influenced ‘Christian vote’. However, historical experience in Argentina shows that launching into politics is full of obstacles. Some of the most important innovations introduced by Neo-Pentecostalism – as the fastest-growing expression of the Evangelical world – are linked to the consolidation of megachurches in middle- and high-class neighbourhoods and the training of Evangelical leaders on a large scale. Both these innovations develop in correlation with a shift of the Gospel towards the ‘world’ and the need for social change; that is, a Christian call to transform the environment. This article aims to explore the political implications of Evangelical leadership in megachurches located in Buenos Aires, Argentina. This work is based on original materials, compiled for a research project using ethnographic techniques such as participant observation, in-depth interviews and documentation review.